Morbillivirus infection in cetaceans stranded along the Italian coastline: pathological, immunohistochemical and biomolecular findings - DI GUARDO, Giovanni; DI FRANCESCO, Cristina Esmeralda; Eleni C; Cocumelli C; Scholl F; Casalone C; Peletto S; Mignone W; Tittarelli C; Di Nocera F; Leonardi L; Fernández A; et al. (Research in Veterinary Science, 2013)
Morbilliviruses are recognized as biological agents highly impacting the health and conservation status of free-ranging cetaceans worldwide, as clearly exemplified by the two Dolphin Morbillivirus (DMV) epidemics of 1990-1992 and 2006-2008 among Mediterranean striped dolphins (Stenella coeruleoalba). After these two epidemics, morbilliviral infection (MI) cases with peculiar neurobiological features were reported in striped dolphins stranded along the Spanish coastline. Affected cetaceans showed a subacute-to-chronic, non-suppurative encephalitis, with brain lesions strongly resembling those found in human "subacute sclerosing panencephalitis" and "old dog encephalitis". Brain was the only tissue in which morbilliviral antigen and/or genome could be detected. Beside a case of morbilliviral encephalitis in a striped dolphin's calf stranded in 2009, we observed 5 additional MI cases in 2 striped dolphins, 1 bottlenose dolphin (Tursiops truncatus) and 2 fin whales (Balaenoptera physalus), all stranded in 2011 along the Italian coastline. Noteworthy, 3 of these animals (2 striped dolphins and 1 bottlenose dolphin) showed immunohistochemical (IHC) and/or biomolecular (PCR) evidence of morbilliviral antigen and/or genome exclusively in their brain, with 1 striped dolphin and 1 bottlenose dolphin also exhibiting a non-suppurative encephalitis. Furthermore, simultaneous IHC and PCR evidence of a Toxoplasma gondii coinfection was obtained in 1 fin whale. The above results are consistent with those reported in striped dolphins after the two MI epidemics of 1990-92 and 2006-2008, with evidence of morbilliviral antigen and/or genome being found exclusively in the brain tissue from affected animals.